2022
DOI: 10.1097/01.jmq.0000753240.14141.87
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Disposition and Clinical Outcomes After Spine Surgery

Abstract: Objective: Spinal decompression with or without fusion is one of the most commonly performed procedures in spine surgery. However, there is limited evidence on the effect of discharge environment on outcomes after surgery. The purpose of this study is to identify the effects of discharge disposition setting on clinical outcomes after spine surgery. Methods: Patients who underwent lumbar decompression, lumbar decompression and fusion, or posterior cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Patients discharged home were found to have significantly higher preoperative functional scores 40 . Similar studies found lower PROM scores for those discharged to post-acute rehabilitation facilities 41-43 . By implementing preoperative PROMs, orthopaedic surgeons can identify patients who are not yet ideal candidates for an elective procedure if the goal is for discharge home.…”
Section: Clinical Opportunitiessupporting
confidence: 57%
“…Patients discharged home were found to have significantly higher preoperative functional scores 40 . Similar studies found lower PROM scores for those discharged to post-acute rehabilitation facilities 41-43 . By implementing preoperative PROMs, orthopaedic surgeons can identify patients who are not yet ideal candidates for an elective procedure if the goal is for discharge home.…”
Section: Clinical Opportunitiessupporting
confidence: 57%
“…While not the principal investigation of the present analyses, we found that patients discharged to healthcare facilities were less likely to be readmitted or re-present to the hospital following elective lumbar spine surgery. Prior research has reported similar observations following spine surgery, [54] although other studies have reported no association between discharge disposition and hospital readmission risk [ 52 , 55 ].…”
Section: Discussionmentioning
confidence: 76%
“…In the recent study, the rehabilitation might play a role as an independent predictor for the wound complications after lumbar fusion surgery. 36 Even the current metaanalysis did not survey the wound complications, the improvement of disability and pain might be related to the factor. However, a recent study reported that discharged to rehabilitation and discharged to home showed a statistically similar postdiswww.e-neurospine.org 287 charge morbidity status.…”
Section: Discussionmentioning
confidence: 89%